2014
DOI: 10.3168/jds.2014-8611
|View full text |Cite
|
Sign up to set email alerts
|

Evolution under different storage conditions of anomalous blue coloration of Mozzarella cheese intentionally contaminated with a pigment-producing strain of Pseudomonas fluorescens

Abstract: Several widespread occurrences of anomalous blue coloration of Mozzarella cheese have been recorded in the United States and some European countries. Official laboratory analysis and health authorities have linked the occurrences to contamination of the processing water with strains of Pseudomonas fluorescens, although several experts questioned how to unequivocally link the blue color to the presence of the microorganism. To establish a method to determine whether a given Pseudomonas spp. strain is responsibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 5 publications
5
22
0
Order By: Relevance
“…population is close to 8 log cfu/g of cheese. This result is in accordance with the previous studies (Sechi et al, 2013;Cenci-Goga et al, 2014) where the authors correlated the appearance of the anomalous blue coloration of mozzarella cheese to a specific P. fluorescens cell number, thus confirming the reliability of the method here described.…”
Section: Discussionsupporting
confidence: 92%
“…population is close to 8 log cfu/g of cheese. This result is in accordance with the previous studies (Sechi et al, 2013;Cenci-Goga et al, 2014) where the authors correlated the appearance of the anomalous blue coloration of mozzarella cheese to a specific P. fluorescens cell number, thus confirming the reliability of the method here described.…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with other studies [30], the isolation of P. fluorescens-related microorganisms from the water sample and from the labelling gun suggests the importance of good sanitization procedures. The abnormal coloration observed on the carcasses started from the label inoculation point, indicating that the carcass contamination was probably due to the labelling gun.…”
Section: Discussionsupporting
confidence: 91%
“…Accordingly, the labelling gun should be disinfected frequently during slaughtering operations, to improve gun cleaning and decontamination when labelling the carcasses. As previously suggested [30], the alteration induced by P. fluorescens was directly correlated to storage time in addition to environmental temperature. In the two butcher shops under investigation, there was a longer storage time in the cold rooms (of about five days) before sale than in the other butcher shops, where the carcasses were stored for less than 24/36 h. Moreover, bacterial load seems to play a role in the appearance time of the alteration.…”
Section: Discussionsupporting
confidence: 68%
“…In 2010, the Italian agricultural authorities found that some BM from an area south of Rome (Italy) had fallen below standards after traces of cow's milk were found; moreover, anomalous blue colouration of Mozzarella cheese contaminated with a pigment-producing strain of Pseudomonas fluorescens has been reported (Cenci-Goga et al, 2014 Many investigations have been carried out to characterise BM. They dealt with establishing methods to detect the addition of cow's milk to buffalo milk in mozzarella preparation (Addeo et al, 1995), and with characterising its microbiological profile (Coppola et al, 1988;Romano, Ricciardi, Salzano, & Suzzi, 2001;Ercolini et al, 2012).…”
Section: Introductionmentioning
confidence: 99%